Effect of cytokinins on oxidative stress in tobacco plants under nitrogen deficiency - Rubio-Wilhelmi, M.M.; Sanchez-Rodriguez, E.; Rosales, M.A.; Begoña, Blasco; Rios, J.J.; Romero, L.; Blumwald, E.; Ruiz, J.M. (Environmental and experimental botany, 2011)
► N-deficiency-induced senescence, the rise in ROS trigger oxidative stress. ► Transgenic plants expressing IPT gene coding the rate-limiting step in CKs synthesis. ► WT plants under N-limited, reduced biomass and increased the generation of ROS. ► Transgenic plants under N-limited, did not produce high ROS and maintained biomass. ► The expression of P SARK∷IPT in plants could improve nitrogen use efficiency. Wild type and transgenic tobacco plants expressing isopentenyltransferase, a gene coding the rate-limiting step in cytokinin synthesis, were grown under limited nitrogen (N) conditions. Our results indicated that the WT plants subjected to N deficiency displayed reduced biomass and relative growth rates, increased levels of oxidative damage and reduced foliar concentrations of the different N forms. However, the transgenic plants expressing P SARK∷IPT, in spite of showing a significant decline in all the N forms in the leaf, avoided the alteration of the oxidative metabolism and maintained biomass and the relative growth rates at control levels, under suboptimal N conditions. These results suggest that the increased cytokinin synthesis in the transgenic plants is an effective mechanism to improve N-use efficiency.